2017
DOI: 10.1016/j.jmau.2017.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of electromagnetic fields exposure on the antioxidant defense system

Abstract: Technological devices have become essential components of daily life. However, their deleterious effects on the body, particularly on the nervous system, are well known. Electromagnetic fields (EMF) have various chemical effects, including causing deterioration in large molecules in cells and imbalance in ionic equilibrium. Despite being essential for life, oxygen molecules can lead to the generation of hazardous by-products, known as reactive oxygen species (ROS), during biological reactions. These reactive o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
138
1
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(147 citation statements)
references
References 143 publications
2
138
1
6
Order By: Relevance
“…However, the methanol extract (12.98 mg EDTAE/g) was the least active metal chelator. Indeed, transition metals, such as iron, can participate in Fenton reaction, converting hydrogen peroxide that is produced from mitochondrial oxidative respiration, into highly toxic hydroxyl free radical [40]. In the current study, the ethyl acetate extract, rich in flavonoids, showed the highest metal chelating properties (Table 3).…”
Section: Resultsmentioning
confidence: 55%
“…However, the methanol extract (12.98 mg EDTAE/g) was the least active metal chelator. Indeed, transition metals, such as iron, can participate in Fenton reaction, converting hydrogen peroxide that is produced from mitochondrial oxidative respiration, into highly toxic hydroxyl free radical [40]. In the current study, the ethyl acetate extract, rich in flavonoids, showed the highest metal chelating properties (Table 3).…”
Section: Resultsmentioning
confidence: 55%
“…Auch der ATHEM-Report bestätigt oxidativen Zellstress als Wirkmechanismus [7]. In ihrem Review von 2017 sichteten Kivrak und Kollegen 162 Studien, die nicht nur deutlich zeigten, "dass die EMF-Exposition oxidativen Stress in verschiedenen Geweben auslöst, sondern auch, dass sie signifikante Veränderungen der Blut-Antioxidanzien-Marker verursacht" [40]. Mit folgenden Auswirkungen: "Müdigkeit, Kopfschmerzen, verminderte Lernfähigkeit und kognitive Beeinträchtigungen gehören zu den durch EMF verursachten Symptomen."…”
Section: Die Erklärung: Oxidativer Zellstress Durch Elektromagnetischunclassified
“…Mit folgenden Auswirkungen: "Müdigkeit, Kopfschmerzen, verminderte Lernfähigkeit und kognitive Beeinträchtigungen gehören zu den durch EMF verursachten Symptomen." Ergänzend wird vorgeschlagen, "verschiedene Antioxidantien wie Vitamin E, Melatonin und Folsäure (zu) verwenden, um die möglichen negativen Auswirkungen einer EMF-Exposition zu verhindern" [40].…”
Section: Die Erklärung: Oxidativer Zellstress Durch Elektromagnetischunclassified
“…Exposure to electromagnetic fields may cause adverse biological effects on the functioning of living organisms, e.g. induce oxidative stress and apoptosis, affect neural functions in the human brain, or functioning of the reproductive system [1][2][3]. It should also be noted that long-term exposure to an electromagnetic field, even if of low strength, may influence people's well-being [4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%